Pediatric Stainless-Steel Crown Cementation Finite Element Study - Waly, Ahmed S.; Souror, Yasser R.; Yousief, Salah A.; Alqahtani, Waleed M.S.; El-Anwar, Mohamed I. (European Journal of Dentistry, 2020)
Objective To study the effect of using different cement types under pediatric stainless-steel crown (SSC) around mandibular second primary molar using three-dimensional (3D) finite element analysis.Materials and Methods A 3D finite element model was built for pediatric mandibular molar by laser scanning of natural extracted tooth. Four types of cement (zinc phosphate, glass ionomer, resin-modified glass ionomer, and resin) of 200 μm layers thickness were tested under a stainless-steel crown of 130-μm thickness. Twelve case studies were reported within this research, as the applied load of 330 N was tested with three angulations: vertical, oblique at 45°, and laterally.Results Linear static stress analysis was performed. The resultant stresses and deformations' distribution patterns did not change with cement type, while the values were altered. All deformations and stresses were found within the normal range.Conclusions Analysis results indicated that using stiffer cement material increases tooth structure stresses and reduces crown body stresses and deformations, while bone was nearly insensitive to cement type.
Keywords: Hall technique; stainless steel crown; finite element; cement; zinc phosphate; glass ionomer